2008
DOI: 10.1002/rcm.3707
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric investigation of the sequence selectivity for adduction of heterocyclic aromatic amines on single‐strand oligonucleotides

Abstract: Heterocyclic aromatic amines (HAAs) generated during the cooking of meats are known to be genotoxic substances able to form covalent bonds with DNA bases after metabolic activation. This work aimed at the investigation of the influence of the local environment of nucleobases along the nucleotidic sequence on its modification induced by two different HAAs, namely 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) and 2-amino-3-methylimidazo[4,5-f]quinoline (IQ), in order to identify possible sequences more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This is not absolutely accurate since HAA and other alkylating agents do show a modest sequence selectivity in terms of their formation and repair. However, the selectivity for HAA’s and small alkylating agents is not at CpG sequences. DNA repair can also be impacted by sequence but the effect is relatively small and cannot explain the remarkable preference for CpG and CpApG sequences . As mentioned above, the frequency of truncating G → T transversions in APC is below what would be predicted due to random mutations and not elevated as predicted if HAA’s adducts were a cause of mutated APC (Table ).…”
Section: Discussionmentioning
confidence: 93%
“…This is not absolutely accurate since HAA and other alkylating agents do show a modest sequence selectivity in terms of their formation and repair. However, the selectivity for HAA’s and small alkylating agents is not at CpG sequences. DNA repair can also be impacted by sequence but the effect is relatively small and cannot explain the remarkable preference for CpG and CpApG sequences . As mentioned above, the frequency of truncating G → T transversions in APC is below what would be predicted due to random mutations and not elevated as predicted if HAA’s adducts were a cause of mutated APC (Table ).…”
Section: Discussionmentioning
confidence: 93%
“…It was observed that IQ preferred 5′-GGG-3′ sequences, while PhIP preferred 5′-GGA/G/T-3′ trinucleotides, with the site of adduction being the center guanine base. 239 …”
Section: Mass Spectrometry-based Mapping Of Nucleobase Damage Alonmentioning
confidence: 99%
“…238 Jamin et al utilized ESI-MS/MS to study the effects of different bases flanking on the 3′ or 5′ side of a guanine base on its reactivity towards heterocyclic aromatic amines, 2-amino-1methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) and 2-amino-3methylimidazo[4,5-f ]quinoline (IQ). 239 Model oligonucleotides (5′-TTTTTXGYTTTT-3′, where X and Y can be either C/ A/G/T) were incubated with activated HAAs, and the reaction mixtures were directly analyzed using HPLC-MS/MS. It was observed that IQ preferred 5′-GGG-3′ sequences, while PhIP preferred 5′-GGA/G/T-3′ trinucleotides, with the site of adduction being the center guanine base.…”
Section: Mass Spectrometry-based Mapping Of Nucleobase Damage Along D...mentioning
confidence: 99%
“…In 2008, Jamin et al [86] investigated the influence of the local environment and neighboring base effect on the adduction of HAAs, specifically PhIP and IQ on T-rich model single-strand oligonucleotides. Similarly, Chan et al [87] reported an electrospray ionization tandem mass spectrometry method for the identification and position mapping of unmodified and aristolochic acid modified (5′-TTTATT-3′, 5′-TTTGTT-3′ and 5′-TACATGTGT-3′) oligonucleotides.…”
Section: Mass Spectrometry In the Analysis Of Oligonucleotide Adductsmentioning
confidence: 99%